2009
DOI: 10.1093/humrep/dep271
|View full text |Cite
|
Sign up to set email alerts
|

The value of measuring anti-Mullerian hormone in women with anovulatory polycystic ovary syndrome undergoing laparoscopic ovarian diathermy

Abstract: Pretreatment circulating AMH level seems to be a good predictor of the ovarian response to LOD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
95
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 19 publications
14
95
1
1
Order By: Relevance
“…Our group and several other researchers have previously reported a significant reduction in serum anti-Müllerian hormone (AMH) after LOD (Weerakiet et al 2007, Amer et al 2009, Elmashad 2011 Reproduction (2017) 154 R13-R21…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our group and several other researchers have previously reported a significant reduction in serum anti-Müllerian hormone (AMH) after LOD (Weerakiet et al 2007, Amer et al 2009, Elmashad 2011 Reproduction (2017) 154 R13-R21…”
Section: Introductionmentioning
confidence: 90%
“…of serum AMH was missing as data were presented as median and range (Amer et al 2009, Sunj et al 2014a. The mean ± s.d.…”
Section: Study Selectionmentioning
confidence: 99%
“…Finally, earlier studies have found that increased AMH levels in PCOS are not only correlated with the increased number of small preantral follicles, but also to some intrinsic abnormality of granulosa cell function (24). These findings may signify that in some way, AMH levels express the severity of the disorder probably reflecting the severity of derangement in folliculogenesis (24). Also, these data are similar but different from other data that in women undergoing laparoscopic ovarian diathermy, the women who became ovulatory had lower levels of serum AMH before treatment (25).…”
Section: Figurementioning
confidence: 87%
“…In addition, in PCOS, serum levels of AMH generally correlate with serum androgens and with insulin (21-23), which also relate to the more severe phenotypes. Finally, earlier studies have found that increased AMH levels in PCOS are not only correlated with the increased number of small preantral follicles, but also to some intrinsic abnormality of granulosa cell function (24). These findings may signify that in some way, AMH levels express the severity of the disorder probably reflecting the severity of derangement in folliculogenesis (24).…”
Section: Figurementioning
confidence: 92%
See 1 more Smart Citation